2016
DOI: 10.1186/s13048-016-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of rutin against metabolic, biochemical and hormonal disturbances in polycystic ovary syndrome in rats

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is the most prevalent endocrinopathy in women of reproductive age. The study was commenced to assess the favorable effects of Rutin against metabolic, biochemical, histological, and androgenic aspects of polycystic ovary syndrome in rats.MethodsFemale Sprague-Dawley rats were administered letrozole (1 mg/kg) per orally (p.o) for a period of 21 days for the induction of PCOS, followed by dose of rutin (100 mg/kg and 150 mg/kg, p.o) for 15 days using 0.5% w/v CMC as veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 44 publications
7
51
0
Order By: Relevance
“…Our results reproduced the findings of previous studies where PCOS induced group showed significant increase in serum level of triglyceride (TG), total cholesterol (CH), low density lipoprotein (LDL) and significant decrease in high density lipoprotein (HDL) [35,36]. Previous studies [37,38] attributed imbalances in lipid profile in PCOS to hyperandrogenemia as confirmed in our study by the significant increase in the Figure 6.…”
Section: Discussionsupporting
confidence: 92%
“…Our results reproduced the findings of previous studies where PCOS induced group showed significant increase in serum level of triglyceride (TG), total cholesterol (CH), low density lipoprotein (LDL) and significant decrease in high density lipoprotein (HDL) [35,36]. Previous studies [37,38] attributed imbalances in lipid profile in PCOS to hyperandrogenemia as confirmed in our study by the significant increase in the Figure 6.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress may be engaged in the pathogenesis of PCOS (47). Induced oxidative stress in ovaries by LTZ (48) was similar to that observed in natural PCOS (6). Our results indicated a significant increase in MDA level and reduction in GSH activity.…”
Section: Discussionsupporting
confidence: 85%
“…The hormonal statistics of letrozole induced rats embodied a hyper-androgenized state responsible for abnormal ovarian physiology [ 18 ]. The disruption in usual hypothalamic pituitary gonadal axis, elevate both testosterone and LH and developed a disease state [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, plant extracts are being widely used to treat female reproductive disorders [ 16 , 17 ]. Flavonoids are plant based compounds which are of great interest due to their expansive pharmacological activities [ 18 ]. Quercetin (3,5,7,3′,4′-pentahydroxyflavone) is a flavonoid [ 19 ], ubiquitously present in fruits and vegetables especially tomato, onion, broccoli, lettuce, grapes, apple and blueberries [ 20 ].…”
Section: Introductionmentioning
confidence: 99%